optical patterns controlled by computerized spatial light modulator - naser, hayder (Al-Qadisiyah Journal of Pure Science, 2020)
In this work, a contemporary optical system is designed using a technology of spatial light modulator (SLM). This system is depending on the ability of altering light beam into different optical patterns according to a signal feedback injected computationally to the SLM. The effects of control parameters on the SLM operation are studied such us brightness (B) which determines the constant DC voltage applied to SLM pixels, and contrast (C) determines the maximum AC voltage amount that can be applied to the SLM. The influences of the transmission linearity of image intensity are controlled by the gamma adjustment which can be used to align non linearity of image intensity. The grey scale is used to control and imagine which signals corresponding to grey levels and image location. The resolution and orientation of the obtained images are altered by the screen format to make optical experiments more satisfied, hence different ratios of amplitude and phase modulation can be understood.